Awareness of the Health Effects of Smoking Among Secondary School Students in Benghazi City. - H. Belkheir, Samira; F. El-mani, Souad; J. Al werfalli, Amina (Benghazi University Medical Journal, 2025)
Background: Increasing public awareness of the health risks associated with tobacco smoking is one of the most effective strategies for reducing tobacco use. Aim: To assess the level of awareness about the health risks of smoking among secondary school students in Benghazi City. Methods: A cross-sectional study was conducted involving male secondary school students .in Benghazi. Results: The study included 345 students their mean age was 16.9±0.83 years. Prevalence of smoking in students was 12.8%, while 5.2% were ex-smoker and 82% never smoke. Rate of smoking decrease by increasing the level of father’s education. Mean age of starting smoking was 13.5±2.1years, 18.2% of current smoker start smoking at age ≤10years.Current smoker 77.3% of them their friends were smoker.More than half ( 56.8% ) of current smoker their fathers were smoker .Opinion of student about smoking , 86.9% they were sure about the effect of smoking to health ,about the effect of their friends on acceptability of smoking only 7% were sure ,69.3% of student sure about harmful effects of passive smoking , only half ( 52.3%) of smoker had desire to quit smoking .The range of their knowledge about Harmful effects of smoking was 93% for Cardiovascular diseases and lung cancer to 50% for male infertility . Majority tried to stop smoking (81.8%). Source of information about smoking was 41.7% from family &friends. Conclusion: This study demonstrates the significance of parents’ educational attainment in relation to their children’s smoking behavior. The presence of a family member who smokes at home has an impact on this influence. Additionally, it demonstrates that when teenagers are young and spend a lot of time with their friends, the actions of those who smoke have a big impact on the others. The majority of students knew that smoking cigarettes has health risks.